Effect of supplemental Vitamin E on the performance, metabolic profiles, and immune responses of dairy calves - P.G. Reddy; J.L. Morrill; H.C. Minocha; M.B. Morrill (Kansas Agricultural Experiment Station Research Reports, 1984)
Forty-six Holstein heifer calves were used from birth to 3 rno to study the effect of supplemental vitamin E at 1400 or 2800 mg dl-a.-tocopherol acetate given orally at weekly intervals or 1400 mg dl-a-tocopherol by intramuscular injection. Weekly starter consumption was 10 to 27 % more (P=.12) and weekly weight gains were 9 to 25% more (P=.13) in supplemented calves. Creatine phosphokinase activity was negatively correlated with serurn tocopherol concentrations, indicating a subclinical muscular dystrophy in unsupplemented calves. Lymphocyte stimulation indices were positively correlated with serum tocopherol concentration. Calves given high level of oral supplementation had higher IgM antibody concentration. It was concluded that supplemental vitamin E is beneficial for calves reared on conventional complete starters to increase disease resistance and to obtain optimum performance.; Dairy Day, 1984, Kansas State University, Manhattan, KS, 1984;
Keywords: Kansas Agricultural Experiment Station contribution; no. 85-116-S; Report of progress (Kansas Agricultural Experiment Station); 460; Dairy; Vitamin E; Performance; Metabolic profiles; Immune response